Flux Peaking of 7-12 keV Deuterons at Channelling in TiD2 Crystal and Enhancement of Neutrons Yield in d(d,n)3Hе Reaction; Charged and Neutral Particles Channeling Phenomena - Tukhfatullin T. A. Timur Ahatovich; Pivovarov Yu. L. Yuriy Leonidovich; Kuznetsov S. I. Sergey Ivanovich; Eykhorn Yu. L. Yury Leonidovich; Dudkin G. N. Gennadiy Nikolaevich (2016, 2016)
Title screen